Murine Blastocysts Release Mature MicroRNAs Into Culture Media That Reflect Developmental Status - Hawke, David Connor; Ahmed, Danyal Baber; Watson, Andrew John; Betts, Dean Harvey (Frontiers in Genetics, 2021)
Extracellular microRNA sequences derived from the preimplantation embryo have attracted interest for their possible contributions to the ongoing embryonic-uterine milieu as well as their potential for use as accessible biomarkers indicative of embryonic health. Spent culture media microdroplets used to culture late stage E4.0 murine blastocysts were screened for 641 mature microRNA sequences using an RT-qPCR-based array. We report here 39 miRNA sequences were exclusively detected in the conditioned media, including the implantation-relevant miR-126a-3p, miR-101a, miR-143 and miR-320, in addition to members of the highly expressed embryonic miR-125 and miR-290 families. Based on these results, a microRNA panel was assembled comprising of 5 members of the miR-290 family (miR-291-295) and 5 conserved sequences with significance to the embryonic secretome (miR-20a, miR-30c, miR-142-3p, miR-191, miR-320). Panel profiling of developing embryo cohort lysates and accompanying conditioned media microdroplets revealed extensive similarities in relative quantities of miRNA sequences and, as a biomarker proof-of-concept, enabled reliable distinction between media conditioned with differently staged embryos (zygote, 4-cell and blastocyst). When used to assess media conditioned with embryos of varying degrees of degeneration, the panel revealed increases in all extracellular panel sequences, suggesting cell death is an influential and identifiable factor detectable by this assessment. In situ hybridization of 3 panel sequences (miR-30c, -294, -295) in late stage blastocysts revealed primarily inner cell mass expression with a significant presence of miR-294 throughout the blastocyst cavity. Furthermore, extracellular miR-290 sequences responded significantly to high centrifugal force, suggesting a substantial fraction of these sequences exist within a vesicle such as an exosome, microvesicle or apoptotic bleb. Together, these results support the use of extracellular microRNA to assess embryonic health and enable development of a non-invasive viability diagnostic tool for clinical use.